Examining the Relationship between Writing Habits, Digital Literacy, and Students’ Perceptions in AI Writing Feedback and Critical Writing Skills among Senior High School Students - Oclarit, DC Jane; Barcelona, Kriscentti Exzur (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined how writing habits mediate the relationship between digital literacy, students’ perceptions of AI writing feedback, and critical writing skills among senior high school students. Anchored in the sociocognitive theory of writing, the research explored the interaction of cognitive, behavioral, and technological factors in writing development. A descriptive correlational design was employed involving 167 Grade 11 Humanities and Social Sciences students from a private Catholic institution. Data were collected using validated Likert-scale questionnaires and a rubric-based writing task, and analyzed through descriptive statistics, multiple regression, and structural equation modeling (SEM). Findings revealed that students demonstrated high perceptions of AI writing tools in terms of usefulness and ease of use, but only moderate trust. Writing habits and digital literacy were rated high to very high, while critical writing skills were at an approaching proficient level across clarity, reasoning, analysis, and reflection. Results further showed that digital literacy and perceptions of AI significantly influence writing habits; however, these variables do not directly predict critical writing skills. The best-fitting structural model indicated that critical writing development is primarily associated with higher-order cognitive processes rather than routine writing practices alone. The study concludes that while AI tools and digital competence enhance writing engagement, the development of critical writing skills requires deliberate cognitive and instructional support. It recommends strengthening explicit instruction in higher-order thinking, integrating AI tools critically, and designing curricula that emphasize reasoning and reflection. The study aligns with SDG 4 (Quality Education) by promoting inclusive and effective digital learning practices. It contributes to sustainability by supporting responsible AI integration, strengthening institutional teaching practices, and developing critical competencies essential for academic success and future employability.
Keywords: Artificial intelligence writing feedback; Critical writing skills; Digital literacy; Senior high school students; Structural equation modeling; Writing habits